Surface Quality of Fe, Ni and Cr added Hyper-eutectic Al-Si Automotive Alloys under Up-milling and Down-milling Operation - Akib Abdullah Khan; Mashiur Rahman Shoummo; Mohammad Salim Kaiser (Universitas Negeri Malang, 2022)
Effect of the elements Fe, Ni, and Cr on the surface quality under machining of hyper-eutectic aluminium-based Al-Si automotive alloys has been carried out as the elements improve the properties of this alloy. Machining is done on a horizontal type milling machine using a high-speed steel slab milling cutter in dry condition. Only the cutting speed varies throughout the experiment, while the machining feed and depth of cut remain fixed. The experimental results show that the addition of these alloying elements increases the roughness and hardness specially due to formation of Fe-rich intermetallic . However, the needle-like has been refined with the addition of Cr, as seen by the microstructure. The SEM fractography shows a huge cleavage of the brittle phase, which initiates the crack propagation for Fe added alloys. The downward force causes compressive stress exerted in down-milling operation, so the results depict higher hardness and better surface finish. Besides, shorter chips are formed in down-milling than up-milling process, which rather causes the brittleness of the alloys. When the cutting speed is raised, the surface quality deteriorates due to high temperature, while the hardness improves initially due to formation of precipitates then decreases due to coarsening of precipitates.